I = ∫ 0 π x 3 ln sin x d x k = ∫ 0 π x 2 ln ( 2 sin x ) d x
Let the two integrals be defined as given above. If I can be written as I = C A π B k , where A , B and C are positive integers with A and C being coprime integers. Find A + B + C .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Be careful with your notation. IE In the question you already introduced I 1 , but in your solution, you redefine it to I and then introduce another I 1 term. That can be confusing to someone glancing through the solution.
The solution would be slightly better presented as using a reduction formula to calculate ∫ x n ln sin x to build out I 1 , I 2 , I 3 , I 4 .
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Definite Integrals
Let I = ∫ 0 π x 3 ln sin x d x
Using properties of Definite Integrals, ∫ 0 a f ( x ) d x = ∫ 0 a f ( a − x ) d x I = ∫ 0 π ( π − x ) 3 ln sin x d x = ∫ 0 π ( π 3 − 3 π 2 x + 3 π x 2 − x 3 ) ln sin x d x = ∫ 0 π π 3 ln sin x d x + ∫ 0 π − 3 π 2 x ln sin x d x + ∫ 0 π 3 π x 2 ln sin x d x + ∫ 0 π − x 3 ln sin x d x = I 1 + I 2 + I 3 + I 4
Now, I 1 = π 3 ∫ 0 π ln sin x d x , which is a standard integral ∫ 0 π ln sin x d x = 2 ∫ 0 π / 2 ln sin x d x = − π ln 2
So, I 1 = − π 4 ln 2
Taking I 2 , using a formula I that I proved in my previous question , ∫ 0 π x f ( sin x ) d x = 2 π ∫ 0 π f ( sin x ) d x ⇒ I 2 = − 3 π 2 ∫ 0 π x ln sin x d x = − 2 3 π 3 ∫ 0 π ln sin x d x = 2 3 π 4 ln 2
For I 3 , we use ln a b = ln a + ln b , ln sin x = ln ( 2 sin x ) − 2 1 ln 2 I 3 = 3 π ∫ 0 π x 2 ln sin x d x = 3 π ∫ 0 π x 2 ( ln ( 2 sin x ) − 2 1 ln 2 ) d x = 3 π k − 2 3 π ∫ 0 π ln 2 d x = 3 π k − 2 π 4 ln 2
Now, simple I 4 = − I
Hence, I ⇒ 2 I I = − π 4 ln 2 + 2 3 π 4 ln 2 + 3 π k − 2 1 π 4 ln 2 − I = π 4 ln 2 ( − 1 + 2 3 − 2 1 ) + 3 π k = 2 3 π k